Trends in primary school dropout and completion rates in the pastoralist Turkana County, Kenya - Migosi, Joash; Nanok, Daniel; Ombuki, Charles; Metet, Joseph (Transnational Research Journals, 2012)
The status of education in Turkana County is typical of all Arid and Semi Arid Lands (ASAL) Counties of Kenya characterised by low enrolment levels, high dropout rates and poor infrastructural development. This study was undertaken to investigate pupils’ access and participation in primary school education in Kakuma and Lokichoggio divisions of Turkana County in north western Kenya. The purpose of the study was to determine the enrolment and completion rates of primary schools in Turkana County, using Kakuma and Lokichoggio divisions as case study representation. Stratified random sampling was employed to select nine schools from the two divisions’ schools. The research study employed the descriptive survey design. The data collection instruments utilised included questionnaires administered to head teachers and teachers. Focus group discussions conducted for pupils and parents and interviews done for the key informants and head teachers. The data collected was analysed qualitatively using descriptive statistics. The study revealed that although completion rates were still low compared to national figures, pupils’ access and participation in primary school education was slowly and steadily improving in the area of study where the two divisions were experiencing rising enrolment levels in primary schools. About 60% of the pupils in the 23 public primary schools in the area of study were enrolled in boarding schools. The study makes several recommendations to boost the completion rates in Turkana County. These recommendations range from building more boarding schools and provision of adequate supply of food schools among others. Key words: Trends, Primary School, Dropout, Completion Rates, Pastoralist, Turkana County, Kenya